Unveiling the therapeutic and insecticidal potential of dangling coneflower: A comprehensive study - Abhiram, S; Jobi, X (Plant Science Today, 2026)
Newly described plant species represent valuable yet underexplored sources of bioactive compounds. Strobilanthes jomyi (Dangling coneflower) is an endemic species of the Western Ghats, Kerala, India. The current study sought to assess the anthelmintic, insecticidal, antimicrobial and cytotoxic properties of a methanolic extract of S. jomyi leaves, stem and root. Extracts were prepared using Soxhlet extraction and screened using standard in vitro bioassays. All vegetative parts exhibited significant anthelmintic activity, with the leaf extract showing the shortest death time (91.66 ± 2.08 min), followed by root (115 ± 5 min) and stem (115 ± 5 min) extracts. Insecticidal activity was observed only in the leaf extract (100 % at 25 mg/mL). Anti-microbial activity of all vegetative parts of S. jomyi showed mild activity at higher concentrations (10 mg/mL). Cytotoxic evaluation against HeLa, MCF-7 and HT-29 cell lines demonstrated dose-dependent activity, with IC₅₀ values within the range of 10–100 µg/mL. GC-MS results proved the presence of bioactive compounds like n-hexadecenoic acid, stigmasterol, phytol, neophytadiene, tris(2,4-di-tert-butylphenyl) phosphate, Squalene, 1-Eicosanol, lupeol and gamma-sitosterol, which in turn could be responsible for the anthelmintic, insecticidal, anti-microbial and cytotoxic activity of S. jomyi. Taken together, the findings suggest that S. jomyi represents a promising source of bioactive compounds with potential pharmacological and agricultural relevance, warranting further isolation and mechanistic studies.